SIKAP PETANI DALAM MENERIMA MATERI DAN MEDIA PENYULUHAN PERTANIAN DI KELURAHAN SENGKOTEK KECAMATAN LOA JANAN ILIR KOTA SAMARINDA (Farmers Attitude in Accepting the Materials and Medias of Agricultural Extension in Sengkotek Urban Village Loa Janan Ilir Subcity Samarinda City) - AMANDEKA SAPUTRA; TETTY WIJAYANTI; RABIATUL JANNAH (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
Materials and medias of extension are very important in the activities of agricultural extension. The purposes of this research were to know the attitude of farmers in accepting the extension materials and the attitude of farmers in accepting the extension medias.  This research was conducted from May to July 2017 in Sengkotek Urban Village, Loa Janan Ilir Subcity, Samarinda City. Total respondents as many as 32 respondents were determined by proportionate random sampling. The attitude of farmers in accepting the materials and medias of extension was measured by Likert scale. The results show the attitude of farmers to the extension materials is including the category of accept with an average score was 54.78. The attitude of farmers to extension medias is categorized to accept with an average score was 53.66. This can be seen from the attitude of farmers who accept with well language and easily to understand counselors who use the language and the material which presented in the extension activities in accordance with the needs of farmers. In addition, the materials presented in the extension activities already use appropriate medias such as print media (books, brochures, leaflets, and handouts) and audio-visual medias (radio, LCD, and television).